2014
DOI: 10.1080/10926771.2014.864741
|View full text |Cite
|
Sign up to set email alerts
|

Elder Mistreatment among Chinese and Korean Immigrants: The Roles of Sociocultural Contexts on Perceptions and Help-Seeking Behaviors

Abstract: The purpose of this study was to identify dimensions of elder mistreatment in Chinese and Korean immigrant communities and to increase sociocultural understanding of such mistreatment by elucidating the complexities of abuse embedded in unique social and cultural contexts. In-depth interviews were conducted with 20 local professionals working primarily in Asian elderly advocacy, and six focus group discussions were conducted involving 60 community members in the San Francisco Bay area. Five dimensions of elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Sexual abuse, abandonment, and violation of personal rights were not consistently represented among identification of elder abuse subtypes (Dong, Chang, Wong, Wong, & Simon, 2011;Lee, Kaplan, & Perez-Stable, 2014;Yan, 2014b). In addition, transgressing the Chinese value and norm that dictates respect for older adults (Tam & Neysmith, 2006), "disrespect" was perceived as one form of elder abuse, which is different from a western perspective.…”
Section: Perceptions Of Elder Abuse Interventions Help-seeking Tendmentioning
confidence: 84%
See 1 more Smart Citation
“…Sexual abuse, abandonment, and violation of personal rights were not consistently represented among identification of elder abuse subtypes (Dong, Chang, Wong, Wong, & Simon, 2011;Lee, Kaplan, & Perez-Stable, 2014;Yan, 2014b). In addition, transgressing the Chinese value and norm that dictates respect for older adults (Tam & Neysmith, 2006), "disrespect" was perceived as one form of elder abuse, which is different from a western perspective.…”
Section: Perceptions Of Elder Abuse Interventions Help-seeking Tendmentioning
confidence: 84%
“…This disrespectful behavior can give rise to unsettling feelings for victims (Dong, Chang, et al, 2011). Both Lee, Kaplan, et al (2014) and Shibusawa and Yick (2007)'s research participants consider contextual and situational factors when determining elder abuse. For the same elder abuse behavior, non-U.S. born Taiwanese American and U.S. born Chinese Americans had significantly different levels of tolerance (Moon, Tomita, & Jung-Kamei, 2002).…”
Section: Perceptions Of Elder Abuse Interventions Help-seeking Tendmentioning
confidence: 95%
“…In studies conducted in the United States and Europe [18,36,37], a shared living environment was a major risk factor for elder abuse because this increases the opportunities for contact, and thus also conflict and tension. In contrast, Asian studies reported that living alone was associated with an increased risk of elder abuse [24,38]. Therefore, the impact of living alone on the risk of elder abuse may differ according to cultural background.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the impact of living alone on the risk of elder abuse may differ according to cultural background. Lee et al [38] reported that many Korean older persons assume that they will live with, and receive various types of care from, their adult children on the basis of Confucian values and norms; thus, older persons who live alone consider themselves to be neglected.…”
Section: Discussionmentioning
confidence: 99%
“…The bulk of research attention on this topicwas devoted to two groups, Asian American elders (Dong, 2014; Le, 1998; Lee & Shin, 2010; Lee et al, 2011; Lee, Kaplan, & Perez-Stable, 2014; Moon et al, 1998; Moon, Tomita, & Jung-Kamei, 2002; Pablo & Braun, 1998; Yan & Tang, 2001) and African Americans (Benton, 1999; Hudson & Carlson, 1999; Shellman, 2004; Tauriac & Scruggs, 2006). Only a few empirically based research articles on the conceptualization of elder mistreatment had a primary emphasis on Latino (Franco, Gray, Gregware, & Meyer, 2000; Mitchell, Festa, Francis, Juarez, & Lamb, 1999; Paulino, 1998) or American Indian/Alaska Native elders (Hudson, Armachain, Beasley, & Carlson, 1998; Jervis, 2014).…”
Section: Elder Mistreatment and Underserved Groups: What Is Knownmentioning
confidence: 99%